Does Noise Signal Affect Flipping Activities? - Nee, Chong Fen; Ali, Ruhani; Ahmad, Zamri (Universiti Utara Malaysia, 2009)
In this paper, we report the explanatory power of noise signal and fundamentals on flipping activities of share trading. Flipping is defined as the percentage of opening day trading volume divided by the number of shares offered on the first trading day (Miller and Reily, 1987, and Aggarwal, 2003) in an offer for sale. It is affected by investors’ opinion about, for example, the new issue’s future prospect on the first listing day.The initial premium which is defined as the difference between the opening price and the offer price divided by the offer price is used as a proxy for noise signal. Using initial public offers listed on the Main Board of Bursa Malaysia during the period of 1991 to 2003, we find support for the relationship between noise signal and flipping activity in the immediate aftermarket as evident in several models tested as well as the bullish and bearish market models. Among the fundamental factors included in this study, bigger size of offer was found to discourage flipping activities.